FRI0504 Retinotoxicity of hydroxychloroquine; is it possible to demonstrate by spectral domain optical coherence tomography before development? a cross sectional investigation. (23rd January 2014) - çay, H. F.; Erol, M. K.; Turgut Coban, D.; Sezer, I.; Bulut, M.; Cakir, T.; Toraman, N. F.
Abstract : Background: Hydroxychloroquine is an antimalarial drug, which has been used for the treatment of autoimmune disorders as rheumatoid arthritis, connective tissue disease and Sjögren's syndrome. Potential retinotoxicity of the antimalarial drugs is the main limiting issue of their consumption. Objectives: To evaluate the alterations of retinal layers in rheumatic patients, who have been treated with hydroxchloroquine without the signs or symptoms of retinopathy by using spectral domain ocular coherence tomography (SD-OCT). Methods: The retinal layers of patients who have been treated with hydroxychloroquine for rheumatoid arthritis, Sjögren's syndrome and connective tissue diseases and age matched healthy controls were evaluated with SD-OCT. The macular cube protocol, optic disc cube protocol and horizontal and vertical HD five line raster scan protocol were applied. The measured parameters were compared between hydroxychloroquine users and healthy controls and among different diagnostic groups. in addition, correlation of these parameters with drug consumption duration and dose parameters of hydroxychloroquine were performed. Results: A total of 402 eyes of 201 subjects [114 hydroxychloroquine users;40 RA, 47 SjS, 27 CTD and 87 age-mathced healthy females] were evaluated. The central and perifoveal layers and superior and inferior quadrants of retinal nerve fiber layer (RNFL) of hydroxychloroquine users were thinner than of non-users. Connective tissue disease group had longer duration and higher cumulative dose of hydroxychloroquine than other diagnostic groups. This group had thinner mean RFNL values than the other groups as well. There were significant and negative correlations between cumulative dose of drug and first quadrant of full foveal thickness and inferior quadrant of RFNL. Parafoveal and perifoveal layers were correlated negatively with dose of drug per kg of body weight. Conclusions: We did not encounter a significant finding consistent with hydroxychloroquine-induced retinotoxicity. This may be the result of relatively short duration and low cumulative dose of consumed hydroxychloroquine as well as the possible safety of the drug. Nevertheless, peroidic screening should not be ommitted in order to be sure of being not-involving by retinotoxicity. SD-OCT may be the golden standard technique for the follow up of antimalarial-induced retinotoxicity in future. We need further investigation concerning the evaluation of retinotoxicity by SD-OCT Disclosure of Interest: None Declared